OPTIMASI STRUKTUR ATAP TAHAP 1-4 BAJA WF DAN KOMBINASI WF SPACE FRAME TERHADAP BIAYA DAN WAKTU(STUDI KASUS: PROYEK PEMBANGUNAN ISLAMIC CENTER JAMBI) - Indah Puspita Dewi; Ade Nurdin; Putri Nurul Kusum Whardani (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
The roof structure of the Islamic Center Jambi building was initially planned entirely with Wide Flange (WF) steel. However, due to time limitations and tower crane capacity, stages 2–4 were redesigned into a Space Frame system to accelerate construction. This study aimed to analyze the cost and time comparison between a full WF structure (stages 1–4) and a WF–Space Frame combination (WF stage 1, Space Frame stages 2–4). Cost analysis was based on the 2023 Public Works Unit Price Analysis (AHSP), while scheduling was evaluated using the Critical Path Method (CPM). Results showed that the WF–Space Frame combination reduced costs by 11.989% (IDR 35.308 billion vs. 40.118 billion) and shortened project duration by 64 days (348 vs. 412). Therefore, the WF–Space Frame system proved more efficient in both cost and time, making it a more optimal alternative.